EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN FLIPBOOK TERHADAP KETERAMPILAN MENULIS KEMBALI TEKS NARATIF SISWA KELAS V SEKOLAH DASAR - Nurmala, Nurmala; Hodsay, Zahruddin; Pratama, Aldora (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to examine the effectiveness of flipbook learning media in improving fifth-grade students’ ability to rewrite narrative texts at SD Negeri Karang Ringin II. The research employed a quantitative method with a one-group pretest–posttest design. Data on students’ writing skills were collected through pretest and posttest assessments. The data were analyzed using a paired samples t-test to determine significant differences between the two test results. The findings indicated a significant improvement in students’ writing skills after the use of flipbook media. The mean pretest score was 32.47, which increased to 77.72 in the posttest. Statistical analysis showed a significance value of 0.000 (? < 0.05) and a t-value of 13.045, which was greater than the t-table value (1.690). Thus, it can be concluded that flipbook media is effective in improving students’ ability to rewrite narrative texts. The implication of this study is that flipbooks can serve as an innovative and engaging alternative learning media to enhance Indonesian language learning, particularly in developing narrative writing skills at the elementary school level.